Model of terahertz bandpass filter based on ferrofluids - Kochnev, Zahar S. (Russian physics journal)
The paper proposes the bandpass filter model consisting of the geometric model of a cuvette filled with a magnetic fluid. The proposed model is developed using Navier–Stokes equations, level set method, and Maxwell's equations. The numerical simulation is used to study the properties of periodic filamentary structures in the ferrofluid locating in the external magnetic field, depending on the magnetic strength and ferrofluid parameters. Transmission spectra are calculated for the broadband terahertz radiation passing through the created periodic structures. The dependences are suggested and reference points are determined for the formation of periodic structures in the ferrofluid occupying the external magnetic field. A qualitative assessment is conducted for transmission spectra of terahertz bandpass filters.